Analisis Resiko Pekerjaan Dengan Metode Hazard Identification Risk Assesment Di Perusahaan Tambang Batu Bara : Studi Kasus PT Saptaindra Sejati - Yoga Pribadi Putra; Erna Indriastiningsih; Anita Oktaviana Trisna Devi (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
Data from the Social Security Administering Agency (BPJS) for Employment in 2021 - 2022 recorded 499,604 cases of work accidents, then the Circular Letter of the Chief Mining Inspector number: B- 6234/MB.07/DBT.KP/2023 dated 9 October 2023 regarding Increasing Vigilance in Efforts Preventing Mining Accidents and Improving Mining Safety Performance, throughout 2023, 46.9% of accidents will result in deaths due to interaction activities on mine roads. Based on preliminary studies at PT. The true Saptaindra Site SERA in 2023 found that the number of property damage accidents (equipment damage) was 11 cases and near misses were 4 cases. The aim of this research is to identify risks that can occur both in terms of humans, the environment and operational processes, then be able to analyze the level of risk and provide recommendations for controlling dangerous risks to minimize the potential for work accidents at the PT Saptaindra Sejati Site SERA. This research uses HIRA (Hazzard Identification Risk Assessment) method with the main focus being able to identify potential hazards through calculating the level of opportunity (Likelihood) and level of severity (Saverity) in order to obtain the level of risk using a risk matrix. And then control is carried out according to the work safety hierarchy, namely elimination, substitution, engineering, administration and PPE (personal protective equipment). The results of this research show that after controlling jobs with a medium risk level, there are 3 jobs including Topsoil removal, Over burden removal and Coal getting and less than 9 according to table 2.3 Risk Matrix and jobs with a low risk level. risk), namely 3 jobs including Land clearing, Drill and blast and Mine water pumping work in the sump.